CHANGES IN FIBRINOGEN LEVEL IN LIVER CIRRHOSIS - Arif, Saatea; Khan, A Sattar; Khan, Arif Raza (Journal of Ayub Medical College Abbottabad, 2002)
Background: Liver cirrhosis causes significant morbidity and mortality in our country, however early diagnosis prevents complications and carries good prognosis. Estimation of fibrinogen level may be helpful in preventing bleeding tendencies. Methods: Plasma fibrinogen level of 82 confirmed liver cirrhosis in 18-60 years age admitted patients of Khyber Teaching Hospital were determined and compared with normal controls, to establish it as a marker for diagnosis in cirrhosis liver and prognosis. Fibrinogen level was determined by Fibriprest-2. Results: Significantly low levels in patients were recorded as compared to controls. 40% cases showed low fibrinogen level, while nearly 44% had normal levels. Conclusion: Fibrinogen level was low in early and terminal cirrhosis and high in advancing cirrhosis as compared to controls that showed normal levels. KEY WORDS: Cirrhosis, Liver, Fibrinogen.